Cost-effectiveness of cardiovascular imaging for stable coronary heart disease. Issue 5 (14th August 2020) - Walker, Simon; Cox, Edward; Rothwell, Ben; Berry, Colin; McCann, Gerry P; Bucciarelli-Ducci, Chiara; Dall'Armellina, Erica; Prasad, Abhiram; Foley, James Robert John; Mangion, Kenneth; Bijsterveld, Petra; Everett, Colin; et al.
Abstract : Objective: To assess the cost-effectiveness of management strategies for patients presenting with chest pain and suspected coronary heart disease (CHD): (1) cardiovascular magnetic resonance (CMR); (2) myocardial perfusion scintigraphy (MPS); and (3) UK National Institute for Health and Care Excellence (NICE) guideline-guided care. Methods: Using UK data for 1202 patients from the Clinical Evaluation of Magnetic Resonance Imaging in Coronary Heart Disease 2 trial, we conducted an economic evaluation to assess the cost-effectiveness of CMR, MPS and NICE guidelines. Health outcomes were expressed as quality-adjusted life-years (QALYs), and costs reflected UK pound sterling in 2016–2017. Cost-effectiveness results were presented as incremental cost-effectiveness ratios and incremental net health benefits overall and for low, medium and high pretest likelihood of CHD subgroups. Results: CMR had the highest estimated QALY gain overall (2.21 (95% credible interval 2.15, 2.26) compared with 2.07 (1.92, 2.20) for NICE and 2.11 (2.01, 2.22) for MPS) and incurred comparable costs (overall £1625 (£1431, £1824) compared with £1753 (£1473, £2032) for NICE and £1768 (£1572, £1989) for MPS). Overall, CMR was the cost-effective strategy, being the dominant strategy (more effective, less costly) with incremental net health benefits per patient of 0.146 QALYs (−0.18, 0.406) compared with NICE guidelines at a cost-effectiveness threshold of £15 000 per QALY (93% probability of cost-effectiveness). Results were similar in the pretest likelihood subgroups. Conclusions: CMR-guided care is cost-effective overall and across all pretest likelihood subgroups, compared with MPS and NICE guidelines.